FBXO31 modulates activation of hepatic stellate cells and liver fibrogenesis by promoting ubiquitination of Smad7. Issue 8 (3rd November 2019) - He, Huijuan; Dai, Jialiang; Feng, Jialing; He, Qiang; Chen, Xuling; Dai, Wei; Xu, Aizhong; Huang, Haili
Abstract: Liver fibrosis is a critical pathological process in the early stage of many liver diseases, including hepatic cirrhosis and liver cancer. However, the molecular mechanism is not fully revealed. In this study, we investigated the role of F‐box protein 31 (FBXO31) in liver fibrosis. We found FBXO31 upregulated in carbon tetrachloride (CCl4 ) induced liver fibrosis and in activated hepatic stellate cells, induced by transforming growth factor‐β (TGF‐β). The enforced expression of FBXO31 caused enhanced proliferation and increased expression of α‐smooth muscle actin (α‐SMA) and Col‐1 in HSC‐T6 cells. Conversely, suppression of FBXO31 resulted in inhibition of proliferation and decreased accumulation of α‐SMA and Col‐1 in HSC‐T6 cells. In addition, upregulation of FBXO31 in HSC‐T6 cells decreased accumulation of Smad7, the negative regulator of the TGF‐β/smad signaling pathway, and suppression of the FBXO31 increased accumulation of Smad7. Immunofluorescence staining showed FBXO31 colocalized with Smad7 in HSC‐T6 cells and in liver tissues of BALB/c mice treated with CCl4 . Immunoprecipitation demonstrated FBXO31 interacted with Smad7. Moreover, FBXO31 enhanced ubiquitination of Smad7. In conclusion, FBXO31 modulates activation of HSCs and liver fibrogenesis by promoting ubiquitination of Smad7. Abstract : We report that F‐box protein 31 (FBXO31) is upregulated in carbon tetrachloride (CCl4 ) induced liver fibrosis and in activated hepatic stellate cells, induced by transforming growth factor‐β (TGF‐β). The upregulation of FBXO31 enhances activation of HSCs. FBXO31 decreased accumulation of Smad7 in HSCs by promoting ubiquitination of Smad7